"Improving the impact strength of PLA and its blends with PHA in fused layer modelling ". (September 2019) - Ecker, Josef Valentin; Burzic, Ivana; Haider, Andreas; Hild, Sabine; Rennhofer, Harald
Abstract: Poly-(lactic acid) (PLA) is one of the most popular thermoplastics for fused layer modelling (FLM). Due to its semi-crystalline nature, the influences of printing parameters on the properties of the printed part are more complicated than with amorphous thermoplastics like acrylonitrile-butadiene-styrene (ABS). In present study, the influence of the process parameters, such as temperature of the plate as well as printing angle used for the three-dimensional printing process was studied in the case of virgin PLA. In addition, PLA was mixed with an amorphous polyhydroxyalkanoate (PHA) copolymer with the aim to improve its impact properties. Mechanical performance of virgin PLA and its PLA/PHA blend prepared by 3D printing method was compared with the mechanical performance of the parts produced by injection moulding. Small and wide angle X-ray measurements were performed in order to study the influence of the crystal morphology on the mechanics of PLA and PLA/PHA 3D printed as well as injection moulded parts. The PLA/PHA parts produced by 3D printing showed higher impact strength and notched impact strength values than injection moulded parts. Graphical abstract: Image 1 Highlights: Improvement of impact toughness of PLA in fused layer modelling by blending with amorphous polyhydroxyalkanoate copolymers. Process optimization in fused layer modelling was used to further improve impact properties of studied PLA and PLA/PHA blends. PLA/PHA 3D printed samples outperformed notched impact properties of their counter injection moulded parts. An outstanding impact performance of PLA/PHA blends reported in this study could be further used to expand PLA application range.